Average E-Module Pancasila Student Profile Strengthening Projects to Develop Students' Digital Literacy - Jayanti Putri Purwaningrum; Latifah Nur Ahyani; Riawan Yudi Purwoko; Hasan Basri (Jurnal Pendidikan dan Pengajaran, 2024)
Education in Indonesia is entering the era of the digital world where it is a special challenge for schools to be able to keep up with changing times. Teachers and students must be able to keep up with technological developments so that they have digital literacy competencies that are used to operate various learning technologies. The aim of this research is to analyze and describe the stages of development of the e-module project for strengthening the Pancasila student profile (P5) with the theme of local wisdom for elementary school students in phase B. The subjects of this research are elementary school students. The research method used in this research is RnD (Research and Development) with the ADDIE research model. However, in this research the researchers only used the initial stages, namely analysis and design. The results of the independent curriculum analysis show that the researchers designed the creation of e-module media with the theme of local wisdom with the dimensions of the Pancasila student profile being creative, global diversity and independence. Media development is carried out in an effort to increase students' digital literacy. In making the product, researchers used Microsoft Word and Canva software to design the module, then the team carried out the design process through the Heyzine application. There are various product improvement processes to obtain the best design.  The implications of this research are The use of digital technology in this E-Module encourages students to be more active and critical in understanding the material, which in turn improves their digital literacy skills.